Photoassisted Synthesis of Complex Molecular Architectures: Dearomatization of Benzenoid Arenes with Aza‐o‐xylylenes via an Unprecedented [2+4] Reaction Topology. Issue 24 (21st April 2016) - Kuznetsov, Dmitry M.; Mukhina, Olga A.; Kutateladze, Andrei G.
Abstract: A new method was developed for the photoinduced dearomatization of arenes through an intramolecular cycloaddition with aza‐ o ‐xylylenes generated by excited‐state intramolecular proton transfer (ESIPT) in the readily available photoprecursors. The [2+4] topology of this cycloaddition is unprecedented for photo‐dearomatizations of benzenoid aromatic carbocycles. It provides rapid access to novel heterocycles, cyclohexadieno‐oxazolidino‐quinolinols, as valuable synthons for a broad range of post‐photochemical transformations. Abstract : I'm so excited : Photoinduced dearomatization of arenes was achieved through intramolecular cycloaddition with aza‐ o ‐xylylenes generated by excited‐state intramolecular proton transfer in the readily available photoprecursors. The [2+4] topology of this cycloaddition is unprecedented for photo‐dearomatizations of benzenoid aromatic carbocycles and produces the novel heterocycles cyclohexadieno‐oxazolidino‐quinolinols.